Edukasi Tablet Tambah Darah dan Screening Anemia pada Remaja Putri - Rakhmalia Imeldawati; Ainun Ganisia; Nurul Fathiyyah (Health Care : Journal of Community Service, 2026)
Anemia among adolescent girls is a health problem affecting fitness, learning concentration, productivity, and reproductive health readiness. This community service activity aimed to improve adolescents' knowledge of anemia, strengthen understanding of iron tablet consumption, and promote early detection through anemia screening at SMA Nahdlatul Ulama I Gresik. The methods included coordination with school and school health unit staff, educational media preparation, interactive counseling, nutrition education, iron tablet consumption guidance, anemia screening, brief counseling, and evaluation using questionnaires/quizzes and participant feedback. The activity was conducted from 8 to 30 November 2024 with school facility support and teacher/UKS assistance. The results showed improved adolescents' understanding of anemia risks, iron-rich dietary patterns, proper iron tablet consumption, and the importance of periodic health checks. The outputs included an activity report, article draft, and educational media used during implementation. This school-based program may strengthen sustainable prevention of anemia among adolescent girls.